2019
DOI: 10.1021/acs.energyfuels.9b01805
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulation Study on the Effect of Coal Rank and Moisture on CO2/CH4Competitive Adsorption

Abstract: The CO 2 -enhanced coalbed methane recovery (CO 2 -ECBM) technique is based on competitive adsorption. In this study, three models of different coal ranks were established using the molecular dynamics (MD) method. A combination of MD and grand canonical Monte Carlo (GCMC) simulations was used to investigate the competitive adsorption of CO 2 /CH 4 on dry and moist coal. The effects of coal rank and moisture content on pore structure, chemical structure, mixed gas adsorption capacity, and adsorption selectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…One of the common and efficient tools to study the molecular system’s interactions is the radial distribution function (RDF). , To be more specific, this method is used to investigate the possibility of the presence of a chemical type (α) around the other chemical moiety (β) at a specific distance ( r ) from each other. The mathematical definition for RDF is as follows …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the common and efficient tools to study the molecular system’s interactions is the radial distribution function (RDF). , To be more specific, this method is used to investigate the possibility of the presence of a chemical type (α) around the other chemical moiety (β) at a specific distance ( r ) from each other. The mathematical definition for RDF is as follows …”
Section: Resultsmentioning
confidence: 99%
“…In another study, the selective adsorption and selective diffusion of the CO 2 −CH 4 binary mixture in bituminous coal were evaluated by Zhao et al 15 Using GCMC and MD methods, they studied the impacts of temperature, pressure, and bulk mole fraction and suggested an optimal injection depth for CO 2 -ECBM. Li et al 18 used a combination of the MD method and GCMC simulation to investigate the effects of coal rank and moisture on the competitive adsorption of the CO 2 −CH 4 mixture in three different coals. They reported that oxygen-containing functional groups positively impact the selective adsorption of CO 2 , while the presence of moisture has a negative effect on the adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of science and technology, it is becoming a reality to use computer simulations to explain the macroscopic properties from a microscopic point of view [51][52][53][54][55][56][57][58][59]. In particular, MD simulation has proven to be a useful tool for analyzing coal interface properties at the molecular level [60][61][62][63][64][65][66]. Traditional experiments screen flotation agents and dust suppression agents by trial-and-error method.…”
Section: Introductionmentioning
confidence: 99%
“…That is due to the adsorption capacity of the coal matrix on N 2 is weaker than that on CH 4 , thereby CH 4 cannot be displaced through competitive adsorption. 27 Instead, CH 4 desorption is promoted through reducing the CH 4 partial pressure. Previous studies were mainly focused on the effect of CH 4 displacement, and there is a lack of investigation on the dynamic evolution of coal permeability during CH 4 displacement by N 2 injection.…”
Section: Introductionmentioning
confidence: 99%